RANCANG BANGUN APLIKASI BELAJAR PEMROGRAMAN DENGAN GAME EDUCATION PADA SMARTPHONE BERBASIS ANDROID - Putrie Fortuna RGP; Ahmaddul Hadi (Universitas Negeri Padang, 2019)
Programming is a vocational subject in the Vocational School majoring in Software Engineering and Electronics. Programming is classified as a subject that is less desirable and difficult for students, because these subjects are not graphically based and students do not understand the basic structure of the program. And less Affective use of conventional learning resources as the main source of the learning. With the existence of smartphones can be used as an additional source in the world of education. One of them is the use of smartphones as learning media. The purpose of this study is to produce learning media that can help teachers and students in the learning process by loading educational games that can attract students' interest in learning. This application is made using the System Development Life Cycle (SDLC) Prototype method, using an Android-based java programming language, by applying game education algorithms and word game genres where players must arrange random letters into coherent sentences, the random letters will be matched with the answers stored in the database to be the correct answer. The content in the application is the 2013 curriculum syllabus. The material consists of RPP and teaching materials for each basic competency. Ebooks, articles and videos that discuss basic programming. Evaluation is a practice question to measure the level of understanding of students and quiz games in the form of stacking words to train students' memory about basic programming.Keywords: Android, Programming, Game education. word game